2000
DOI: 10.1002/(sici)1521-4095(200004)12:8<569::aid-adma569>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Solution Synthesis of Colloidal Gallium Nitride at Unprecedented Low Temperatures

Abstract: Free‐standing colloids of gallium nitride have been synthesized from azide‐based “single‐source” precursors—molecules that contain both the metal and nitrogen—e.g., [Et2Ga(N3)]3. The solution synthesis is described and the examination of the resulting colloids by dynamic light scattering, transmission electron microscopy, etc. detailed. GaN is an important III–V semiconductor with applications in light‐emitting diodes, lasers, sensors, and high‐temperature electron devices, and it is suggested that in the futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…No GaN was produced in the absence of the capping ligand HDA, which suggests a possible transamination reaction. However, the reaction time was still at least 24 h. Manz et al reported the synthesis of GaN NCs at remarkably low temperature (220 °C) and low reaction time (15–300 min) in triglyme solution using the following organometallic azide precursors: [Et 2 Ga­(N 3 )] 3 , (N 3 ) 2 Ga­[(CH 2 ) 3 NMe 2 ] and (Et 3 N)­Ga­(N 3 ) . Depending on the reaction conditions, several sizes in the range of 2.5 nm up to 500 nm have been obtained.…”
Section: Synthesis Of Different Families Of Semiconductor Nanocrystalsmentioning
confidence: 99%
“…No GaN was produced in the absence of the capping ligand HDA, which suggests a possible transamination reaction. However, the reaction time was still at least 24 h. Manz et al reported the synthesis of GaN NCs at remarkably low temperature (220 °C) and low reaction time (15–300 min) in triglyme solution using the following organometallic azide precursors: [Et 2 Ga­(N 3 )] 3 , (N 3 ) 2 Ga­[(CH 2 ) 3 NMe 2 ] and (Et 3 N)­Ga­(N 3 ) . Depending on the reaction conditions, several sizes in the range of 2.5 nm up to 500 nm have been obtained.…”
Section: Synthesis Of Different Families Of Semiconductor Nanocrystalsmentioning
confidence: 99%
“…10,11,12 Though the synthesis of high quality nanometric sized II-VI semiconductors is already very well established, the synthesis and studies of high quality III-V semiconducting nanocrystals are being increasingly reported in the recent literature. 16,17,18,19,20 III-V semiconductors provide a material basis for a number of already existing commercial products, as well as new cutting edge electronic and optoelectronic devices, like heterostructure bipolar transistors, diode lasers, light emitting diodes, electro-optic modulators 21 and in biology, as fluorescent labels. 22 Hence, it becomes necessary to have an electronic structure model with accurate predictive abilities to describe the quantum confinement effects in these nanocrystals.…”
mentioning
confidence: 99%
“…As shown in figure 3, the spectrum shows a composition consisting of Ga and P and also O, C and N. The presence of C may be attributed to either carbon dioxide adsorption on the surface of GaP nanoparticles or the remains of the solvent [12]. The Ga 3d component centred at 21.4 eV, accorded with the reference value for GaP [13], can be indexed to Ga (III) from GaP.…”
Section: Xps and Esrmentioning
confidence: 91%